PEMBEKALAN PEMBELAJARAN JURNAL PENYESUAIAN BAGI SMK STRADA I - Muliawan, Christopher; Hidajat, Nastasya Cindy (Jurnal Serina Abdimas, 2024)
Educational support activities at educational institutions, especially at Strada I Vocational School, are a form of participation in the transmission of knowledge to schools.aim to provide in-depth knowledge of basic accounting material to prepare for higher education by involving the participation of the MBKM team from Tarumanagara University. This activity contributes to developing education through knowledge of the basics of accounting including general journals, ledgers, trial balances and adjusting journals with deferral type and accrual type. The method of implementing this teaching activity is delivered face to face using Powerpoint media. The results of the MBKM activities for students are adding new knowledge and understanding in the field of accounting related to adjusting journals. After receiving training, it is hoped that students will be mentally prepared to pursue further education.